Peningkatan Hasil Belajar Tema 6 Menggunakan Model Cooperative Learning Tipe Two Stay Two Stray di Kelas V SD - Sahyunan, Sahyunan; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The background of this study is the low student learning outcomes of 16 students only 8 (50.00%) who reached the specified KBM, besides that the average student learning outcomes was 59.12. This study aims to improve integrated thematic learning outcomes through the application of the TSTS learning model. This research is a classroom action research with qualitative and quantitative approaches. The research data in the form of observations and tests, this study was conducted at SDN 03 Ranah Batahan Barat Pasaman. The subjects in this study were class V students with a total of 16 students. This research was conducted in two cycles with four stages, namely planning, implementation, observation and reflection. The results of the study stated that after applying the cooperative learning model TSTS type can improve learning outcomes of integrated thematic learning. This is proven by: (a) The observation of RPP in the first cycle with an average of 85.22% with Good qualifications (B), and Cyclius II 95.45% with Very Good qualifications (AB); teacher activity cycle I with an average of 78.57% with sufficient qualifications (C), and cycle II 96.42% Very Good (AB); Student activities in the first cycle with an average of 78.57% and 96.42% in the second cycle with Very Good (AB) qualifications. (b) student learning outcomes with a percentage that is in the first cycle of meeting 1 and meeting 2 and cycle II, 74.30 (56%), 77.10 (68.75%) and 83.13 (87.5%).